Targeting Solute Carrier Transporters through Functional Mapping. (January 2021) - Colas, Claire; Laine, Elodie
Abstract : Solute carrier (SLC) transporters are emerging drug targets. Identifying the molecular determinants responsible for their specific and selective transport activities and describing key interactions with their ligands are crucial steps towards the design of potential new drugs. A general functional mapping across more than 400 human SLC transporters would pave the way to the rational and systematic design of molecules modulating cellular transport.